Lack of Disease Specificity Limits the Usefulness of In Vitro Costimulation in HIV- and HCV-Infected Patients - Stefanie Kuerten; Tobias R. Schlingmann; Tarvo Rajasalu; Doychin N. Angelov; Paul V. Lehmann; Magdalena Tary-Lehmann (Clinical and Developmental Immunology)
Measurements of antigen-specific T cell responses in chronic diseases are limited by low frequencies of antigen-specific cells in the peripheral blood. Therefore, attempts have been made to add costimulatory molecules such as anti-CD28 or IL-7/IL-15 to ELISPOT assays to increase sensitivity. While this approach has been successful under certain circumstances, results are often inconsistent. To date, there are no comprehensive studies directly comparing the in vitro effects of multiple costimulatory molecules in different disease settings. Therefore, in the present study we tested the effects of IL-7/IL-15, IFN-α, anti-ICOS, and anti-CD28 on antigen-specific T cell responses in patients infected with HCV or HIV versus healthy individuals. Our data show that none of the aforementioned molecules could significantly increase ELISPOT sensitivity, neither in HCV nor in HIV. Moreover, all of them caused false-positive responses to HCV and HIV antigens in healthy individuals. Our results question the broad use of in vitro costimulation.